TAFSIR AL-QUR’AN ATAS PROBLEMATIKA LINTAS AGAMA:: Kajian Atas Tafsir Tarjuman Al-Qur’an Karya Mawlana Abul Kalam Azad - Toipah, Toipah (QOF, 2017)
This article discusses the book of tafsir, Tarjuman al-Qur’an, by Mawlana Abul Kalam Azad (W. 1958 AD). Azad is one of the commentator (of the Qur’an) and politicians who were born in the minority in India, where India is a predominantly Hindu country. In this case, Azad wants Islam and Hinduism to co-exist. Azad thought is considered controversial because the Islamic reformers in India, we can call Sayyid Ahmad Khan who crave a separate country that became a home for Muslims. Azad has an offer of interpretation that is different from other commentators of his time related to the unity of religions. From here the authors formulate some problems. First, how is the anatomy of the Tarjuman al-Qur’an and what the methodology used by Azad in his interpretation ?. Secondly, what does Azad offer to the multicultural problems of religion ?. To answer that question, the writer uses approach of comparative study between book of interpretation. The method used in writing this article is descriptive-comparative. In his interpretation, Azad is not only interpreting a single conviction, but rather a variety of beliefs, such as the concept of al-din and illah. He interprets the Qur’an by emphasizing the unity of religion that he thinks. The interpretation is of course based on the context that colored him at the time of compilation of the interpretation.